Determining the liabilities of internet service providers in cyber defamation: a comparative study (2016)
The need to protect free speech as a right and the need to protect the reputations of others are two often conflicting legal positions which need to be balanced. The internet is a medium where free speech can be carried out and equally creates a space where reputations can be injured. Damage to reputation can lead to defamatory action being taken against the author, publisher or any other contributor to the publication of the defamatory statement. To facilitate communications on the internet the roles played by the internet service providers or intermediaries cannot be underestimated. And often times, the intermediaries are made the sole defendant or joined as a party to defamatory suits. The UK and the US are seen as laboratories for defamatory actions on the internet. Also, India and South Africa have responded through their laws to the problem of determining intermediary’s liability in internet defamation. This research sets out to present a comparative study of the laws in the four nations in determining the liabilities of internet intermediaries, with the hope of discovering the strengths and weaknesses of the law and making suggestions as to the best approach to be adopted in shielding the intermediaries from liabilities and also protecting the reputations of others.